The experiences of women who have used the sub-dermal contraceptive implant (Implanon) and their reasons for the early removal in the Cape Metropole, Western Cape - Hlana, Sylvia Nompucuko (Stellenbosch : Stellenbosch University, 2020)
Thesis (MNur)--Stellenbosch University, 2020.